2018
DOI: 10.1111/1471-0528.15484
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance in adolescents aged 15–16 years born after frozen embryo transfer compared with fresh embryo transfer: a nationwide registry‐based cohort study

Abstract: Objective To assess academic performance in singletons aged 15–16 years conceived after frozen embryo transfer (FET) compared with singletons born after fresh embryo transfer (ET) in Danish cohorts born from 1995 to 2001. Design Danish national registry‐based cohort study. Setting Danish national registries. Population All 6495 singletons conceived after assisted reproductive technology (ART) treatment in Denmark from 1995 to 2001 [FET (n) = 423; fresh ET (n) = 6072]. Methods Mean test scores on a national sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…No difference was found in the adjusted analysis for twins (Spangmose et al 2017) Similar results were found in a large population-based Swedish study of 8,323 ART singletons (Norrman et al 2018). The effect of FET versus fresh ET on the school performance of children was reported in a recent Danish study from the same group and no differences were observed (Spangmose et al 2018).…”
Section: Cognitive Developmentsupporting
confidence: 80%
“…No difference was found in the adjusted analysis for twins (Spangmose et al 2017) Similar results were found in a large population-based Swedish study of 8,323 ART singletons (Norrman et al 2018). The effect of FET versus fresh ET on the school performance of children was reported in a recent Danish study from the same group and no differences were observed (Spangmose et al 2018).…”
Section: Cognitive Developmentsupporting
confidence: 80%
“…Interestingly, our findings were more pronounced in the fresh ET than in the frozen ET group, contrary to a registry‐based study reporting a statistically higher risk of neurodevelopmental delay associated with ART (particularly ICSI using ejaculated sperm with fresh and frozen ET), with higher risk for ICSI with frozen ET, when restricting the analysis to singletons 8 . Nevertheless, no differences were reported between fresh and frozen ET when comparing academic performance in adolescents, in an uncontrolled follow‐up study, in which, however, mild conditions may have been underrepresented 68 . A birth cohort study with a 2‐year follow‐up reported reassuring results for ART, but it was underpowered to detect differences between the fresh and frozen ET modalities 69 .…”
Section: Discussionmentioning
confidence: 93%
“…However, after adjustment for relevant confounders, results were similar in the two groups. Comparisons have also been made between children from IVF and ICSI and between children from fresh and frozen cycles (10)(11)(12), with similar results.…”
Section: Cognitive Developmentmentioning
confidence: 90%